Expression of functional c-kit receptors rescues the genetic defect of W mutant mast cells. - Alexander, W S (1991)
Loss-of-function mutations in the gene for the c-kit tyrosine kinase receptor are strongly implicated in the developmental abnormalities of W mutant mice. To dissect further the relationship between kit and the W phenotype, retroviruses carrying the normal murine c-kit gene were constructed. In infected cells, the level of c-kit expression from these vectors varied markedly with different promoter elements, the 5' viral LTR proving to be the most effective. When introduced into cells which normally do not express c-kit, ectopic kit receptors transduced a ligand (Steel factor)-dependent proliferative signal in IL-3-dependent DA-1 myeloid cells and induced transformation in fibroblasts. Primary mutant mast cells were used to examine the effects of reconstituting functional kit expression in cells affected by W mutations. Exogenous c-kit expression rescued the defective proliferative response to Steel factor of cells from both W/Wv and W/W mutant mice. Moreover, functional kit expression also restored the capacity of W/Wv mast cells to survive and differentiate in vivo. These results imply that defective c-kit receptor function is sufficient to generate the W mutant phenotype.